Information Analysis of Biochemical Parameters for Glucose Tolerance Tests - Sokol, Yevgen I.; Chmykhova, Oksana V.; Boyko, V. V.; Zamyatin, P. N.; Zamiatin, D. P. (Springer Nature Switzerland AG, 2020)
In the vast majority of existing methods of obtaining parametric biomedical information, it is represented by a finite set of informative parameters (features). Their informational significance is always different and practically not evaluated for the tasks of parametric identification and diagnosis of diabetes mellitus. In this paper, it is proposed to evaluate the informational significance of parameters (features) based on dispersion analysis of changes in their mathematical expectation with respect to residual noise. Fisher’s F-statistics were used as a quantitative measure of the changes, with the subsequent conversion of the obtained data into the amount of information expected based on the equations of the information measurement theory.

У переважній більшості існуючих методів отримання параметричної біомедичної інформації вона представлена кінцевим набором інформативних параметрів (особливостей). Їх інформаційне значення завжди різне і практично не оцінюється для завдань параметричної ідентифікації та діагностики цукрового діабету. У даній роботі пропонується оцінити інформаційну значимість параметрів (особливостей) на основі дисперсійного аналізу змін їх математичного очікування по відношенню до залишкового шуму. F-статистика Фішера використовувалася в якості кількісної міри змін, з подальшим перетворенням отриманих даних в обсяг очікуваної інформації на основі рівнянь теорії інформаційних вимірювань.
Keywords: glucose tolerance testing; glycemic dynamics; regression model; analysis of variance; F-statistics; correlation; глюкозотолерантний тест; глікемічна динаміка; регресійна модель; дисперсійний аналіз; F-статистика; кореляція